The Influence of Brand Image on The Purchase Decision of Eiger Products Study of Students of The Faculty Of Social Sciences & Law Universitas Negeri Makassar - Asdi Suprianto; Hasnawi Haris; Aris Baharuddin; Haedar Akib; Cudai Nur (Fakultas Ilmu Sosial dan Hukum, 2025)
This study aims to determine how much influence Brand Image Influence has on Eiger Product Purchase Decisions (Case Study of Students of the Faculty of Social Sciences and Law, State University of Makassar). This study uses a quantitative method with a type of quantitative descriptive research. Data collection techniques used are observation, questionnaires and documentation. The population in this study was 4,160 people. The sampling method used was using the random sampling formula, which was narrowed by 100 people. The data obtained from the research results were processed using the SPSS 25 application which consisted of validity and reliability tests, descriptive data analysis techniques and regression tests.Based on the research results obtained from the descriptive analysis that the Brand Image variable is in the very good category with supporting indicators namely brand identity, brand personality, brand associations, brand attitudes and behavior, and brand benefits and advantages. For the Purchase Decision variable which is in the very high category, most choose to agree on indicators of stability in a product, habits in buying products, providing recommendations to others, and making repeat purchases. Based on the test of the coefficient of determination R2 is at a very high interval, which means that brand image has a very high influence on the Eiger Bag Purchasing Decision for Students of the Faculty of Social Sciences and Law, Makassar State University.